Mutation in OsCADT1 enhances cadmium tolerance and enriches selenium in rice grain. Issue 3 (3rd February 2020) - Chen, Jie; Huang, Xin‐Yuan; Salt, David E.; Zhao, Fang‐Jie
Summary: How cadmium (Cd) tolerance in rice is regulated remains poorly understood. We used a forward genetic approach to investigate Cd tolerance in rice. Using a root elongation assay, we isolated a rice mutant with enhanced Cd tolerance, cadt1, from an ethyl methanesulphonate (EMS)‐mutagenized population of a widely grown Indica cultivar. The mutant accumulated more Cd in roots but not in shoots and grains. Using genomic resequencing and complementation, we identified OsCADT1 as the causal gene for the mutant phenotype, which encodes a putative serine hydroxymethyltransferase. OsCADT1 protein was localized to the nucleus and the OsCADT1 gene was expressed in both roots and shoots. OsCADT1 mutation resulted in higher sulphur and selenium accumulation in the shoots and grains. Selenate influx in cadt1 was 2.4 times that of the wild‐type. The mutant showed higher expression of the sulphate/selenate transporter gene OsSULTR1;1 and the sulphur‐deficiency‐inducible gene OsSDI1 . Thiol compounds including cysteine, glutathione and phytochelatins were significantly increased in the mutant, underlying its increased Cd tolerance. Growth and grain biomass were little affected. The results suggest that OsCADT1 acts as a negative regulator of sulphate/selenate uptake and assimilation. OsCADT1 mutation increases Cd tolerance and enriches selenium in rice grains, providing a novel solution for selenium biofortification.